2016
DOI: 10.2147/ott.s105198
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-126 regulates proliferation and invasion in the bladder cancer BLS cell line by targeting the <em>PIK3R2</em>-mediated PI3K/Akt signaling pathway

Abstract: ObjectiveTo assess whether microRNA-126 (miR-126) targets phosphatidylinositol 3-kinase regulatory subunit beta (PIK3R2) and to determine the potential roles of miR-126 in regulating proliferation and invasion via the PIK3R2-mediated phosphatidylinositol 3 kinase (PI3K)-protein kinase B (Akt) signaling pathway in the human bladder BLS cell line.Materials and methodsA recombinant lentivirus (Lv) vector expressing miR-216 (Lv-miR-126) was successfully constructed, and Lv-miR-126 and Lv vector were transfected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Some microRNAs have tumor-suppressing role in cancers and their expression is down-regulated in most types of cancers including BC. miR-126 is one these microRNAs whose decreased expression in BC is associated with increased cell proliferation, migration and invasiveness [ 71 ]. Multiple targets of miR-126 have been discovered until now and their modulation by miR-126 has negative effects on BC cell viability.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Some microRNAs have tumor-suppressing role in cancers and their expression is down-regulated in most types of cancers including BC. miR-126 is one these microRNAs whose decreased expression in BC is associated with increased cell proliferation, migration and invasiveness [ 71 ]. Multiple targets of miR-126 have been discovered until now and their modulation by miR-126 has negative effects on BC cell viability.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
“…Multiple targets of miR-126 have been discovered until now and their modulation by miR-126 has negative effects on BC cell viability. For instance, down-regulation of ADAM-9 mRNA causes inhibition of cell invasiveness [ 72 ] and by targeting PIK3R2 gene it modulates PI3K/Akt pathway and has a negative impacton cell’s proliferation [ 71 ]. MiR-125b-5p is another tumor suppressive miRNA.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Components of the PI3K/Akt/mTOR signaling pathway are commonly upregulated in malignant tumors, and increased Akt phosphorylation is commonly observed ( 19 ). The activation of Akt signaling is associated with cell proliferation, migration and invasion ( 20 ). Notably, it has been reported that NHERF1 inhibits the migration and invasion of human breast cancer cells via the PI3K/Akt signaling pathway ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-27b, miR-24, miR-23b and miR-126* are known to be encoded by the chromosome 9 (5961). In the present study, a considerable number of co-expressed microRNAs in MVs and K562 cells (including hsa-let-7a, hsa-let-7f, miR-126, miR-126*, miR-23b, miR-24, miR-27b and miR-7) were mapped to chromosome 9, while let-7b, miR-1249, miR-130b and miR-185 were mapped to chromosome 22.…”
Section: Discussionmentioning
confidence: 99%